Low Energy and Carbon Hydroponic Tomato Cultivation in Northern Spain: Nutritional and Environmental Assessment - (:unkn) unknown (American Chemical Society, 2024)
The agri-food sector is one of the most impactful on the environment in terms of greenhouse gas emissions and is one of the largest consumers of energy and natural resources. In this context, the objective of this study was to evaluate the environmental ...
Keywords: Hidroponía; Sostenibilidad